Illinois Superconductor Corp : forecasting demand for superconducting filters - Sawhney, Mohanbir; Damkroger, Lisa; McGuirk, Greg; Milbratz, Julie; Rountree, John (London : SAGE Publications Ltd, 2017)
Illinois Superconductor Corp. a technology start-up, came up with an innovative new superconducting filter for use in cellular base stations. It needed to estimate the demand for its filters. The manager came up with a simple chain-ratio-based forecasting model that, while simple and intuitive, was too simplistic. The company had also commissioned a research firm to develop a model-based forecast. The model-based forecast used diffusion modeling, analogy-based forecasting, and conjoint analysis to create a forecast that incorporated customer preferences, diffusion effects, and competitive dynamics.
Originally published: Sawhney, M., Damkroger, L., McGuirk, G., Milbratz, J., & Rountree, J.(1996). Illinois Superconductor Corp: Forecasting Demand for Superconducting Filters. 5-104-033 Evanston, IL: Kellogg School of Management, Northwestern University.
Description based on XML content.
Keywords: elektronické knihy; electronic books; Illinois Superconductor Corp. -- Case studies; Superconductor industry -- Case studies; Superconductors -- Case studies; Electric circuits -- Case studies; Market surveys -- Case studies